The sound of Ahad Analisis Semiotika dalam Film Bilal : A new Breed of Hero - Prasad, Kareena Haya; Fauziyah, Maisa Salma; Azzahra, Salma; Wulandari, Zahwa Syra; Firdaus, Dadan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The animated film Bilal: A New Breed of Hero constructs an articulation locus wherein theological resilience is no longer relegated to an abstract doctrinal space; rather, it transforms into a visual representation that encapsulates the existential struggle of human nature in preserving faith beneath the grip of structured oppression. This investigation is oriented toward conceptualizing the signification of visual signs, dialogic discourse configurations, and the spectrum of symbolic elements to deconstruct the polarization between the subject's metaphysical conviction toward monotheistic principles and the socio-historical repression enforced by the Quraysh power institution, while simultaneously dissecting the phrase "Ahad" as an absolute signifier of theological transcendence. Implementing a descriptive-analytical qualitative research design based on content analysis, this study adopts a multidisciplinary methodological apparatus that synergizes Islamic Theology (Ilmu Kalam), the perspective of the sociology of literature, and semiotic analysis instruments. Theoretically, the argumentative structure is anchored in the taxonomy of Tawhid reconstruction (Rububiyah, Uluhiyah, and Asma wa Sifat) within the corridor of Islamic epistemology, reciprocally synergized with Roland Barthes' triadic signification to unravel semantic penetration at the levels of denotation, connotation, and ideological myth formation. This analytical exploration yields the conclusion that the verbal proclamation of "Ahad" within the narrative corpus constitutes a subversive instrument against the hegemony of oppression, wherein the articulation acts as an emancipatory catalyst for the liberation of human consciousness. On an axiological dimension, this cinematic reconstruction functions as a space for philosophical-religious contemplation, asserting that the principle of tawhid is dialectically intertwined with empirical-social reality, activating critical reason, and constituting a fundamental cornerstone in confronting existential justice distortions.